STRUKTUR DAN KOMPOSISI HUTAN PANTAI KAWASAN WISATA ALAM HATUSUA BEACH NEGERI HATUSUA, KECAMATAN KAIRATU, KABUPATEN SERAM BAGIAN BARAT - Sahupala, Mario; Sahupala, Andjela; Komul, Yulianus (MARSEGU : Jurnal Sains dan Teknologi, 2024)
Research on the structure and composition of the coastal forest in the Hatusua Beach natural tourist area in Hatusua State has the aim of knowing the vegetation potential, both in terms of structure and composition of the forest contained in the coastal forest specifically in the Hatusua Beach natural tourist area in Hatusua State, West Kairatu Seram District. This research was carried out using a survey method combining strip techniques and vertically plotted lines with the coastline. The research results show that structurally there are 5 growth strata, namely strata A, Strata B, Strata C, Strata D, Strata E with each strata having similarities both vertically and horizontally. Meanwhile, the composition of vegetation types in the Hatusua Beach area in the Hatusua State Coastal Forest based on growth level has a number of types including; 9 types of seedlings, 14 types of weaning, 12 types of poles, 18 types of trees. For tall trees ranging from 20 – 31 meters, the important value index value is dominated by Pongamia pinnata with a value of 58.13, Intsia bijuga 41.31, Cerbera manghas 38.86, Tamarindus indica 27.93, and Pterocarpus indicus with a value of 34.55, with a species richness category. According to Shannon winner species diversity, a value of ≤ 1 is categorized as low.